Interactions between active faulting, volcanism, and sedimentary processes at an island arc: Insights from Les Saintes channel, Lesser Antilles arc. (17th July 2016) - Leclerc, F.; Feuillet, N.; Deplus, C.
Abstract: New high‐resolution marine geophysical data allow to characterize a large normal fault system in the Lesser Antilles arc, and to investigate the interactions between active faulting, volcanism, sedimentary, and mass‐wasting processes. Les Saintes fault system is composed of several normal faults that form a 30 km wide half‐graben accommodating NE‐SW extension. It is bounded by the Roseau fault, responsible for the destructive Mw 6.3 21 November 2004 earthquake. The Roseau fault has been identified from the island of Basse‐Terre to Dominica. It is thus 40 km long, and it could generate Mw 7 earthquakes in the future. Several submarine volcanoes are also recognized. We show that the fault system initiated after the main volcanic construction and subsequently controls the emission of volcanic products. The system propagates southward through damage zones. At the tip of the damage zones, several volcanic cones were recently emplaced probably due to fissures opening in an area of stress increase. A two‐way interaction is observed between active faulting and sedimentary processes. The faults control the development of the main turbiditic system made of kilometer‐wide canyons, as well as the location of sediment ponding. In turn, erosion and sedimentation prevent scarp growth at the seafloor. Faulting also enhances mass‐wasting processes. Since its initiation, the fault system has consequently modified the morphologic evolution of the arc through perturbation of the sedimentary processes and localization of the more recent volcanic activity. Key Points: Identification and characterization of submarine active faults and volcanic features in Guadeloupe (FWI) Correlation in time and space between faulting and volcanism with several volcanoes emplaced in damage zones at fault tips Sedimentary processes erase fault‐related topography while faulting control their emplacement